Screening for esophageal squamous cell carcinoma: recent advances - Codipilly, Don C.; Qin, Yi; Dawsey, Sanford M.; Kisiel, John; Topazian, Mark; Ahlquist, David; Iyer, Prasad G. (Gastrointestinal endoscopy, 2018)
Esophageal squamous cell carcinoma (ESCC) is the most common type of esophageal cancer worldwide, with a high mortality due to advanced stage at diagnosis. Although most common in an area known as the Asian Esophageal Cancer Belt, which extends from the Caspian Sea to northern China, and in parts of Africa, high-risk populations also exist elsewhere in the world. Screening for ESCC has been practiced in a few geographic areas and high-risk populations, with varying levels of success. Esophageal squamous dysplasia is recognized as the precursor lesion for ESCC. Endoscopic screening for ESCC/esophageal squamous dysplasia is expensive and not sufficiently available in many high-risk regions. Recent advances in non-endoscopic screening enhanced by biomarker-based disease detection have raised the prospect of improved accuracy and availability of screening for esophageal squamous dysplasia and early stage ESCC. Development of a cost-effective, accurate, and well-tolerated screening test, if applied in endemic areas and high-risk populations, has the potential to reduce mortality from this deadly disease worldwide. In this review, we summarize recent developments in endoscopic and non-endoscopic screening modalities.